2021
DOI: 10.1021/acs.est.1c01604
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Mobility of Contaminants from a Replica Radioactive Waste Trench in Response to Rainfall-Induced Redox Oscillations

Abstract: Results of investigations into factors influencing contaminant mobility in a replica trench located adjacent to a legacy radioactive waste site are presented in this study. The trench was filled with nonhazardous iron- and organic matter (OM)-rich components, as well as three contaminant analogues strontium, cesium, and neodymium to examine contaminant behavior. Imposed redox/water-level oscillations, where oxygen-laden rainwater was added to the anoxic trench, resulted in marked biogeochemical changes includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…These minerals are characterized by specific YREE and Nb signatures produced by hydrothermal processes [24]. These signatures may also be inherited by secondary uranium minerals, which are formed from their decomposition [24][25][26]. However, our results show that the YREE signatures in the secondary minerals studied differ from those of the primary phases.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…These minerals are characterized by specific YREE and Nb signatures produced by hydrothermal processes [24]. These signatures may also be inherited by secondary uranium minerals, which are formed from their decomposition [24][25][26]. However, our results show that the YREE signatures in the secondary minerals studied differ from those of the primary phases.…”
Section: Discussionmentioning
confidence: 59%
“…Similar behavior of Sm is also noted, but not in metatorbernite and torbernite. The formation of a negative anomaly may be related to the presence of REE anionic complexes, which are highly stable and mobile in water solutions [25], and also to the changing redox potential of pore fluids, as a result of which some REEs, i.e., La and Ce, are sensitive to the oxidative properties of fluids [30,31]. Another possible cause of the observed anomaly may be YREE sorption onto iron hydroxides and oxyhydroxides [26].…”
Section: Discussionmentioning
confidence: 99%
“…Iron is the most abundant transition metal element in the Earth's crust, mainly in the form of iron (oxyhydr)oxide minerals, and its global biogeochemical cycling is coupled to various processes in natural environments. 1–5 Due to the low solubility and slow dissolution kinetics of iron (oxyhydr)oxides, their iron dissolution is the rate limiting step for iron participation in global biogeochemical cycling. 6–9 In the natural world, iron dissolution is usually promoted by plants and microorganisms through the release of natural ligands, such as siderophores and low-molecular-weight organic acids with a carboxyl group ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…An unintended consequence of this, is that surface water infiltrates into the more porous trench waste form at a greater rate when compared to the surrounding geology, and during intense and prolonged rainfall events the contaminated water levels in trenches fill up, akin to a ‘bathtub’ ( Payne et al, 2013 , 2020 ). Aside from providing a mechanism enabling the export of contaminants, occurring when trench waters (infrequently) overflow out of the ‘bathtub’ to the surrounding environment ( Payne et al, 2013 ), the periodic influx of oxic waters into these natural reducing zones results in transitory microbial population shifts associated with pronounced elemental cycling ( Vázquez-Campos et al, 2017 ; Kinsela et al, 2021 ). Our previous research showed that the archaeal community in the LFLS waste trenches, while constituting a minor portion of the whole microbial community, included a number of potentially interesting members, either in terms of phylogeny and/or functionality ( Vázquez-Campos et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%